Cash Pooling in Tax Dispute Perspective: Efficiency and Regulatory Challenges - Diastiti, Denis; Rosid, Arifin (E-Jurnal Akuntansi, 2024)
Cash pooling is a cash management strategy that is designed to enhance efficiency. Cash pooling entails transactions with affiliated entities, that can lead to disputes with the tax authorities. The objective of this research is to identify the underlying causes of disputes and to propose strategies for the minimization of such disputes in the future. A qualitative approach was employed, utilizing a case study methodology. This entailed a content analysis of tax court decisions issued between 2021 and 2023 related to cash pooling disputes, complemented by interviews with relevant sources. The analysis identified four principal categories of causes of tax disputes over cash pooling. Disputes occur due to tax auditor factors (competence, communication, proof), taxpayers (documentation and fairness), audit methods (audit guidelines, interpretation of agreements, delineation of transactions), and the absence of domestic regulations related to cash pooling.